Packaging of photonic integrated circuits - Neto, Hugo Daniel Barbosa (2019)
With the continuous evolution of optical communication systems, emerged a need for high-performance optoelectronic elements at lower costs. Photonic packaging plays a key role for the next-generation of optical devices. In this work a standard packaging design rules is described, covering both the electrical and optical-packaging exploring both active and passive adjusting techniques, as well as the thermal management of the photonic integrated circuit (PIC). First a process for fiber-to-chip coupling with custom made ball-lensed fibers, is performed and tested initially in a testing-chip and thereafter in a manufactured practical study-case composed by a silicon holder with an InP distributed feedback (DFB) laser. The process of manufacturing etched V-grooves for fiber alignment is approached in detail. After this, for electrical interconnects and radio frequency (RF) packaging, both wire-bonding and flip-chip technique are discussed, and a characterization of the s-parameters in a PIC with wire-bonding is presented. A technique based on ruthenium-based sensors and platinum and titanium-based sensors for thermal control of the PIC is studied and the tested using a custom made PCB designed exclusively for that purpose.